Research and application of aluminum foam materials - ZHANG Hong-ying; OUYANG Ba-sheng; ZHU Guo-jun (Fenmo yejin jishu)
The foamed metals have become the new structural functional materials with the excellent properties of heat, sound, light weight, and energy absorption. Known as the "metal star", the porous aluminum foam is the most popular foam metals with the most potential application, showing the excellent performance as low density, high temperature resistance, good corrosion resistance, non-flammable, good weather resistance, low thermal conductivity, high electromagnetic shielding, high energy absorption, and good noise reduction, which is widely used in the automobile industry, the aeronautics and astronautics industry, and the construction industry. In this paper, the structural characteristics and physical properties of the aluminum foams are reviewed, and the preparation, process principle, and characteristics of the aluminum foams are summarized.